Improving Of Sports Mental Education Training For Central Java Rowing Athletes To Sports Week Of North Sumatera - Aceh 2024 - Sungkowo, Sungkowo; Sobihin, Sobihin; Alfarizi, M. Rizky; UN, Rizam Ahada; Setiono, Aris; Pasya, Ahnaf Kamal; Israel, Yefta; Firmanyah, Ario Rizky (Jurnal Abdimas, 2024)
The purpose of the study is to create and improve performance both subjectively and objectively even under challenges, overcoming stress, anxiety and decisions related to match situations. The results of the community service research of 8 Pelatda rowing athletes on Resilience: 5 athletes in the high category, 3 athletes in the very high category. On Psychological Tension: 1 athlete in the high category, 7 athletes in the very high category. On Mental Skills: 4 athletes in the high category, 4 athletes in the very high category. Discussion on Resilience, athletes are given recommendations: high and very high categories, then Maintain the ability and skills in managing emotions, tension, and adapting to various situations, On Psychological Tension, athletes are given recommendations: Need to practice controlling emotions, thinking practically, focusing on the match, and thinking positively. If you really can't do it independently, you should contact the psychological team to get counseling related to this. Mental Skills athletes are given recommendations: Maintain the ability and skills in managing thoughts, and adapting to various situations.